2017
DOI: 10.3748/wjg.v23.i25.4615
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenic multifocal ulcerous stenosing enteritis: Radiologic features and clinical behavior

Abstract: AIMTo investigate the characteristic radiologic findings of cryptogenic multifocal ulcerous stenosing enteritis (CMUSE) which can be differentiated from other similar bowel disease and to assess their clinical behavior.METHODSTwenty pathologically and clinically confirmed CMUSE patients (males:females = 8:12; mean age: 40.4 years) between March 2002 and August 2015 from seven academic centers in South Korea were retrospectively reviewed. We evaluated small bowel series (SBS; n = 25), computed tomography (CT) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…Moreover, we believe that there might have been cases of CEAS misdiagnosed as CMUSE or other disorders, especially in Asian countries like Korea and China. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we believe that there might have been cases of CEAS misdiagnosed as CMUSE or other disorders, especially in Asian countries like Korea and China. 8 …”
Section: Discussionmentioning
confidence: 99%
“…7 CTE or magnetic resonance enterography can be used in the diagnosis of CMUSE, showing an increased enhancement of intestinal mucosa, short segmental stenoses and a slightly thickened intestinal wall; however, short stenoses can easily be missed. 8 The small intestinal ulcers in CMUSE are shallow and flat.…”
Section: Retrieval Of Retained Capsule Endoscopy By Device-assisted Ementioning
confidence: 99%
“…At present, intestinal stenoses can be treated with DAE. 8 Several studies have demonstrated that endoscopic balloon dilation (EBD) using DBE for small intestinal strictures is effective and safe. 7 Based on our findings, EBD may be considered as a first-line treatment option for CD patients with small intestinal stenoses to reduce the need for surgical intervention over the patient's lifetime, unless F I G U R E 2 In Case 2, A, A capsule endoscopy showed scarred ulcers and stenoses in the small intestine.…”
Section: Retrieval Of Retained Capsule Endoscopy By Device-assisted Ementioning
confidence: 99%
“…45,46 Multifocal stenosing ulcerations are known in Crohn's, vasculitis, radiation enteritis, and cryptogenic multifocal ulcerous stenosing enteritis (CMUSE) among other conditions. 47 CMUSE is defined as unexplained small intestinal multiple strictures and ulcerations of unknown origin and is thought to be an atypical form of vasculitis. It is seen in middle-aged patients with no evidence of systemic inflammation.…”
Section: Differential Diagnosismentioning
confidence: 99%